Little century - Keesey, Anna, 1962- (New York : Farrar, Straus and Giroux, 2012)
In the lawless frontier town of Century, Oregon, Esther Chamber is met by her distant cousin, a laconic cattle rancher named Ferris Pickett. But this town on the edge of civilization is in the midst of a very real range in a story of dispossession, greed, and ecstatic visions of America.
Keywords: Orphans -- Fiction; Rangelands -- Oregon -- Fiction; Avarice -- Fiction; Violence -- Fiction; Ranch life -- Fiction; Frontier and pioneer life -- Fiction; Cousins -- Fiction; Oregon -- Fiction; Historical fiction; Western stories; Historical fiction; Western stories